Dasatinib ameliorates chronic pancreatitis induced by caerulein via anti-fibrotic and anti-inflammatory mechanism. (September 2019) - Zeng, Xiang-Peng; Wang, Li-Juan; Guo, Hong-Lei; He, Lin; Bi, Ya-Wei; Xu, Zheng-Lei; Li, Zhao-Shen; Hu, Liang-Hao
Graphical abstract: Abstract: Chronic pancreatitis (CP) is characterized by persistent inflammation and fibrosis of the pancreas. To date, no clinical therapy is available to reverse the inﬂammatory damage or pancreatic fibrosis associated with CP. This study systematically investigated the effect of Dasatinib, a multiple tyrosine kinases (TKs) inhibitor, on pancreatic fibrosis and inflammation in vivo and in vitro. We found that Dasatinib notably ameliorated pancreatic fibrosis and infiltration of macrophages in a model of caerulein-induced murine CP. Further RNA-seq and phosphoproteomic analysis and in vitro validation assays indicated that Dasatinib exerted a marked inhibition on the proliferation and activation of PSCs, which may be resulted from increased GSK3β-mediated β-catenin cytosol retention by inhibiting upstream multiple TKs (such as PDGFR and Src) and MAPK cascades (including ERK1/2 and p38 MAPK). In addition, Dasatinib significantly restrained both the M1 and M2 polarization of macrophages, and impeded its recruitment and crosstalk with PSCs. Our findings indicated that Dasatinib is a potential anti-inflammatory and anti-fibrotic therapeutic strategy for CP.